Becoming Muslim in Imperial Russia Conversion, Apostasy, and Literacy - Kefeli, Agnes Nilufer (Cornell University Press, 2014)
Winner of the Association for Slavic, East European, and Eurasian Studies' Reginald Zelnik Book Prize in History. Through close study of Russian, Eurasian, and Central Asian ethnographic, administrative, literary, and missionary sources, this book shows how traditional Islamic education among the people of Tsarist Russia's Middle Volga region (today's Tatarstan) helped to Islamize the area's Turkic peoples, setting the stage for the development of modernist Islam in Russia."Agnes Nilufer Kefeli's thorough and imaginative use of sources is notable. She makes use of Russian official sources from the State Archives of Tatarstan and elsewhere, but she also consults a broad range of nonarchival Islamic sources, including Tatar-language Arabic-script popular literature. This makes the book highly original and important to both Russian history and Islamic studies."-Allen Frank